A sequence-based phylogenetic inference using a bayesian-based model - Mohd Nawawi, Shazana (2017)
Phylogenetic methods play an important role in inferring protein classification from protein information i.e. sequence and structure. For this study, we construct a phylogenetic tree using MrBayes and validate the reliability of the phylogenetic tree with the "gold standard" protein classification (SCOP). There are five step involved to produce phylogenetic tree, which are retrieving the data from protein data bank (PDB), do a multiple sequence alignments, identification of model parameter, build the phylogenetic tree using MrBayes and last but not least is validate the tree with the gold standard (SCOP) Classification. Protein sequence alignments is a step in molecular evolutionary analysis that is used for estimating divergence and commonly used for identifying protein functions. However, the resulting alignments produced from conventional method become less accurate when the sequence identity between protein pairs decrease (Rosenberg, 2005). MrBayes consists of some advantages as compared to another techniques of phylogenetic inference. The result is easy to analyze and it has computational advantages like speed (J P Huelsenbeck & Ronquist, 2001 ). Previous studies (Grone & Maruska, 2016) (Muller, Rahmann, Dandekar, & Wolf, 2004) have shown that MrBayes produced accurate and robust phylogenetic classification for low similarity proteins (<40% PID). To conclude MrBayes has been proposed as one of the best method to classify the distantly related protein.